Aligning health supply chain maturity with technology transfer in low-and-middle-income countries - Steele, Pamela; Tolani, Foyeke; Subramanian, Lakshmy (Acta Scientific, 2019)
Background: Technological advancement has been very rapid in low-and-middle-income countries (LMICs), facilitating economic growth and removing structural challenges. However, there is still much to be achieved as the developing world is in the phase of adapting existing technologies, rather than pursuing innovations and creating new technology. In this context, many of the LMICs still lack social infrastructures like power and maintenance culture to help sustain the consistent and efficient use of these technologies. Technology affects public health supply chains (PHSC) mainly through automation, connectivity for last-mile delivery, and the level of innovation. Technologies like Logistic Management Information System (LMIS), RFID (radio-frequency identification), mobile phone technology, blockchain, etc have the potential to make existing PHSC more robust. Purpose: This study aims to conceptually elucidate the constraints of the introduction of technology in PHSC of LMICs. Some of these countries do not recognize the absorptive capacity that must be in place to enable the diffusion of technology. In the absence of such capacity, major challenges can arise in a country after the technology transfer takes place. Therefore, to overcome this gap in the literature, we attempt to understand the role of technology transfer in PHSC of LMICs and focus on identifying the appropriate supply chain maturity stage that technology should be introduced to improve healthcare outcomes. Methodology: We attempt to understand the appropriate stage for introducing technology in PHSC through the review of existing literature on broader themes. We searched the Google Scholar and Science Direct databases for studies that focussed on the right maturity stage of PHSCs for the transfer of technology. The review includes forty-seven studies encompassing four studies on healthcare supply chains, seven on economic development, ten on technology transfers, six on innovation, five on how different models of technology transfer impact regional growth, and fifteen on the evolution and importance of maturity models in improving supply chain performance. Our detailed review supported our use of the Frontier Markets Supply Chain Maturity Model (MM), as proposed by the Bill and Melinda Gates Foundation, for further analysis, since it is based on the identification of the weakest links in LMIC supply chains and it is widely used in their context. Finding: The frontier market maturity model is a reference framework that identifies dynamically shifting bottlenecks and helps supply chain teams know where to focus their improvement efforts for the maximum impact on supply chain performance. Our study elucidates how technology can be best used depending on the maturity stage of the health supply chains in LMICs. We identified leadership, collaboration, local capacity building, etc as some of the “key determinants for success” to enhance a country’s absorptive capacity to strengthen the PHSC through technology. When the maturity model stages were mapped with the key determinants, we found that countries can use the technology differently depending on their capacity. At the canvas stage, the LMICs can absorb the technology and can optimally utilize it at the bronze stage. LMICs can exploit the imported technology at the silver stage leading to better integration at the gold stage. Finally, in the graduated stage, LMICs are more adept at realizing the full potential of technology and harnessing it for context-driven solutions. Conclusion: An important consideration is that technology should be relevant to the country’s capabilities and factor endowments. The introduction of technology does not necessarily bring immediate benefits. The benefits will depend on countless factors that vary across countries. If an LMIC uses technology for its development, it will have from the beginning human and capital resources for the new technologies, avoiding the problem of all the developed countries that must channelize more time and effort presently to reskill their workforces that have been trained on old technologies. The study underlines that key drivers like participation, benchmarking, developing capacity, and allocating financial resources judiciously will help in creating an enabling environment for better use of technology.
Keywords: LMICs; PHSC; RFID